2014
DOI: 10.1371/journal.pone.0094269
|View full text |Cite
|
Sign up to set email alerts
|

Development of Safe and Effective RSV Vaccine by Modified CD4 Epitope in G Protein Core Fragment (Gcf)

Abstract: Respiratory syncytial virus (RSV) is a major cause of respiratory tract infection in infants and young children worldwide, but currently no safe and effective vaccine is available. The RSV G glycoprotein (RSVG), a major attachment protein, is an important target for the induction of protective immune responses during RSV infection. However, it has been thought that a CD4+ T cell epitope (a.a. 183–195) within RSVG is associated with pathogenic pulmonary eosinophilia. To develop safe and effective RSV vaccine us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Both IFN-γ- and IL-17A-expressing cells were significantly fewer following RSV B G peptide stimulation (Fig 5B) as compared to those seen following RSV A2 G peptide stimulation after RSV A challenge (Fig 4B). These results indicate that a.a. residues 183–195 of the RSV B G protein do not play roles as CD4 + T-cell epitopes, as previously reported [29]. Consequently, CD4 T-cell responses for the RSV B subtype were not found in our study.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Both IFN-γ- and IL-17A-expressing cells were significantly fewer following RSV B G peptide stimulation (Fig 5B) as compared to those seen following RSV A2 G peptide stimulation after RSV A challenge (Fig 4B). These results indicate that a.a. residues 183–195 of the RSV B G protein do not play roles as CD4 + T-cell epitopes, as previously reported [29]. Consequently, CD4 T-cell responses for the RSV B subtype were not found in our study.…”
Section: Resultssupporting
confidence: 71%
“…It was previously shown that a.a. residues 183–195 of GcfA functions as a CD4 T-cell epitope that is necessary for induction of a strong antibody response, while the same region of GcfB lacks T-cell epitope functionality and induces a relatively weak antibody response [29]. Thus, we reasoned that fusion of the GcfA sequence to the GcfB sequence might simultaneously provoke T-cell activity against both GcfA and GcfB, and thus, that immunization with the GcfAB fusion antigen might induce strong humoral responses against both subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations